The Era-Based Classification of the Jurisprudential Levels of the Mujtahidin of the Hanafis - Salah Abu-Alhaj (My University, 2016)
In this study, I have striven to prove that the era-based classification (al-taqsim al-zamani) for the ranking of the levels (tabaqat) of the scholars of jurisprudence (fuqaha’) is foremost in understanding the different stages of fiqh and the levels of the fuqaha’ due to the differing of ijtihad from era to era and its development from stage to stage. So, we find that every phase of ijtihad leads to the level which is after it. There wasunbounded and absolute ijtihad (al-ijtihad al-mutlaq), which led to affiliated ijtihad (al-ijtihad al-muntasib), then to ijtihad within a singular school of law (madhhab). There were two forms to al-ijtihad al-mutlaq: The first is the entirely independent mujtahid, embodied and exemplified in Abu Hanifah. The second form is the independent mujtahidwho is affiliated with a madhhab. This form is personified in Abu Yusuf and Muhammad. Next, there is the category of mujtahids that were affiliated with a madhhab (al-mujtahid al-muntasib) in the third and fourth Islamic centuries, namely al-Khassaf, al-Tahawi, al-Karkhi, and al-Jassas. Finally, there is the stage of the mujtahid within a single madhhab (al-mujtahid al-madhhabi), which began after the fourth Islamic century until today. This level of mujtahids has two forms: The mujtahids that came earlier, such as al-Quduri, al-Marghinani, Qadi Khan, and al-Kasani. The second type is of those who came later on, such as IbnHumam, IbnNujaym, and Ibn `Abidin. All of the above scholars of the respective levels of ijtihad share in establishing the differing functions, tasks, and duties of ijtihad, from extracting rulings from primary sources, to giving preponderance to certain jurisprudential rulings over others, tomaking profound decisions in fiqh. However, the mujtahid within a single madhhab does not extract rulings from primary sources. Similarly, the levels of the mujtahids differ in regards to their realizing all of the different tasks of ijtihad.

سعيت في هذا البحث لإثبات أنَّ التقسيم الزماني لطبقات الفقهاء هو الأولى لفهم مراحل الفقه ودرجات الفقهاء؛ لاختلاف الاجتهاد من زمن إلى زمن، وتطوره من مرحلة إلى مرحلة، فنجد كل مرحلة من الاجتهاد توصل لما بعدها، فكان الاجتهاد المطلق ثُمَّ المنتسب ثُمَّ المذهبي، وكان المجتهد المطلق على صورتين: المجتهد المستقل ويتمثل في أبي حنيفة، والمجتهد المستقل المنتسب ويتمثلفي أبي يوسف ومحمد، والمجتهد المنتسب في علماء القرن الثالث والرابع: كالخصاف والطحاوي والكرخي والجصاص، والمجتهد المذهبي بعد القرن الرابع إلى يومنا، وله صورتان: المجتهدون المتقدمون في المذهب: كالقدوريوالمرغيناني وقاضي خان والكاساني، والمجتهدون المتأخرون في المذهب: كابن الهمام وابن نجيم وابن عابدين، والكل مشتركون بالقيام بوظائف الاجتهاد من استنباط وتخريج وترجيح وتمييز وتقرير، إلا المجتهد في المذهب فهو لا يقوم بوظيفة الاستنباط فقط، ودرجاتالمجتهدين متفاوتة في تحقيق كل وظيفة من وظائف الاجتهاد.
التقسيم الزمانيّ لطبقات المجتهدين عند الحنفيّة